Respuesta :

Answer:

x = -3: [tex]y = 10[/tex], x = -2: [tex]y = 4[/tex], x = -1: [tex]y = 0[/tex], x = 0: [tex]y = -2[/tex], x = 1: [tex]y = -2[/tex], x = 2: [tex]y = 0[/tex], x = 3: [tex]y = 4[/tex]

Step-by-step explanation:

Let [tex]y = x^{2}-x-2[/tex], where [tex]x[/tex] and [tex]y[/tex] are the independent and dependent variables, respectively. The approach consists in evaluating the function at values presented in statement:

x = -3

[tex]y = (-3)^{2}-(-3)-2[/tex]

[tex]y = 10[/tex]

x = -2

[tex]y = (-2)^{2}-(-2)-2[/tex]

[tex]y = 4[/tex]

x = -1

[tex]y = (-1)^{2}-(-1)-2[/tex]

[tex]y = 0[/tex]

x = 0

[tex]y = (0)^{2}-(0)-2[/tex]

[tex]y = -2[/tex]

x = 1

[tex]y = (1)^{2}-(1)-2[/tex]

[tex]y = -2[/tex]

x = 2

[tex]y = (2)^{2}-(2)-2[/tex]

[tex]y = 0[/tex]

x = 3

[tex]y = (3)^{2}-(3)-2[/tex]

[tex]y = 4[/tex]